Linearization of power amplifiers with memory effects using memory polynomial and linearly interpolated look-up table predistorter - Saadoon, Mohammed Ayad (2017)
Power Amplifier (PA) plays a vital rule in wireless communication systems, it is used to amplify signal before transmission. Frequently, the PA needs to operate near the saturation region in order to achieve high efficiency power amplification. This will generate nonlinearities in the communication system, these nonlinearities will cause out of band distortion which increases the Adjacent Channel Leakage Ratio (ACLR) and in band distortion which increases the Bit Error Rate (BER). Likewise, the utilization of high spectrally efficient modulation techniques in modern communication systems such as Wideband Code Division Multiple Access (WCDMA) and Orthogonal Frequency Division Multiplexing (OFDM) that have high Peak to Average Power Ratio (PAPR) will be very vulnerable to PA nonlinearities and as the signal bandwidth gets wider, the PA will exhibit memory effects which will cause dynamic distortions in the PA characteristics. Therefore, linearization of the PA is required to overcome these effects. Digital Pre-Distortion (DPD), among all linearization techniques, is a low-cost and efficient method to linearize PAs exhibiting memory effects. However, the recent DPD schemes require time to find the PA inverse characteristics to be predistorted; so, in order to quickly adapt with the dynamic changes in the PA characteristics, a DPD with fast convergence is highly desirable.